Fabrication of MgMoO4-PVA and MgMoO4 fibrous webs via a direct high voltage electrospinning process - Surangkana Wannapop (2018)
Mixtures of (CH3COO)2Mg·4H2O and (NH4)6Mo7O24·4H2O containing 0.7, 1.0 and 1.3 g of poly(vinyl alcohol) (PVA, 125,000 MW) were electrospun by +15 kV direct voltage to form fibrous webs. In the present research, the fibrous web of the 1.3 g PVA was characterized by a thermogravimetric analyser (TGA), and calcined at 400-600 °C for 3 h. MgMoO4contained in the fibrous webs was characterized by X-ray diffraction (XRD), morphologies of the webs by scanning and transmission electron microscopy (SEM, TEM) and atomic force microscopy (AFM), and their vibration modes by Fourier transform infrared (FTIR) and Raman spectrometry. The 5.15 eV direct energy gap, caused by the electronic transition in the (MoO4)2-complex, was determined by UV-visible absorption. Formation mechanism of the fibrous webs was also proposed according to the experimental results. © 2013 Elsevier Ltd.